Short Film Transformation Techniques in Writing Short Stories - John Pahamzah (Journal of English Language Teaching and Cultural Studies, 2022)
The objective of research was to find out there is any significant of using short story toward Indonesian EFL writing skills. Various techniques can be used to make someone skilled at writing short stories. One of them is the film transformation technique. The choice of film transformation techniques must be accompanied by the use of innovative and creative media such as short films. The method used in this study is a quantitative research method using experimental design. The sample used in this study based on the population mentioned above is the 6th semester students of creative writing classes for the academic year 2017/2018. The total sample of students is 30 students, divided into 17 male and 13 female students. Data collection was carried out through two stages, namely pretest and posttest. Based on the analysis results, the result of normality test in pre-test showed t-count (2, 5312) and t-table (11,070), then Ho is refused and Ha is received. The result of normality test in post-test showed t-count (1, 8682) and t-table (11,070), then H0 is refused and H1 is received. The result of homogenity in pretest showed Fcount = 1,228 and Ftable = 1,858. Fcount ≤ F table or 1,228 ≤ 1,858 then Ho is accepted. Moreover, the result of homogenity in posttest showed Fcount = 1.140 and Ftable = 1.858. Fcount ≤ F table or 1,140 ≤ 1,858 then Ho is accepted. The linearity test results from the table can be calculated F ¬ 1.4908 and F table 2.41 with a significant level α = 0.05, then it can be concluded from the results of the linearity calculation of this linear patterned data. The results of hypothesis test showed –table <tcount <ttable or -2.002 <6.09> 2.002, then Ho is rejected and Ha is accepted. To be concluded, there is an influence of the use of film transformation techniques on short story writing skills of creative writing class students in the academic year of 2017/2018, because it obtained an average value with the number of pretest 59.1 and posttest 77.7.